Institutional experience of paediatric high-grade central nervous system tumours: An analysis of 74 patients and review of the literature - Pinarli, Faruk Guclu; Oguz, Aynur; Karadeniz, Ceyda; Okur, Arzu; Sarac, Avni; Baykaner, Kemali; Bora, Huseyin; Poyraz, Aylar (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Although the survival for children with certain central nervous system (CNS) tumour types has improved through current surgical and adjuvant treatment modalities, the prognosis of many high-grade tumours remains poor despite aggressive treatment. The aim of this study is to analyse patients with high-grade brain tumours in our institution to determine the histopathology, clinical characteristics, treatment modalities, and survival. Material and methods : A total of 74 patients with a diagnosis of high-grade brain tumour were analysed. There were a total of 31 patients with embryonal tumours, 27 patients with high-grade glial tumours, 12 patients with brain stem gliomas and 4 patients with other high-grade brain tumours. Results : There were 48 (65%) boys and 26 (35%) girls (ratio: 1.85) with a median age of 99.7 months (range = 2-204 months). The median follow-up period was 19 months (range = 1-204 months). Tumour recurrence was observed in 38 patients (51.4%). The overall survival rate and event-free survival rate of our patients were 27% and 19.5%, respectively. Conclusions : Pediatric high-grade CNS tumours have a very aggressive behaviour and a significant number of children eventually succumb to disease despite multimodal treatment. There is a need of more effective therapeutic approaches for these tumours with poor prognosis. The future improvement in childhood high-grade brain tumour management depends on a better understanding of the molecular genetics and biology of brain tumours.